Business Process Reengineering on Customer Service and Procurement Units in Clinical Laboratory - Dewi Agushinta R.; Anindito Yoga Pratama; Suryadi Harmanto S (Universitas Ahmad Dahlan, 2015)
Existing business processes on a Clinical laboratory located in Bekasi is still run manually. It takes a lot of time to do more process, especially in customer service and procurement units. These inefficient processes are analyzed here. Utilization of information technology (IT) supports operations of company and even improves efficiency and effectiveness of a company. However, the use of information technology must be balanced with readiness of existing resources to operate. Without supporting resources, especially human resources available, information technology is nothing. Business Reengineering Process method used to comprehend the existing business process, determine processes to be reengineered, investigate alternative redesign, simulate the existing business processes and the proposed business processes, performed an analysis of simulation results, and seeking opportunities in corporate using information technology.This Business Process Reengineering (BPR) research helped Clinical laboratory especially in customer service and procurement in improving efficiency and effectiveness of existing processes that will ultimately reduce cost and time. Results showed that business processes increase with information technology utilization and minimize the use of employee.